Kidney transplantation: into the future with belatacept. (December 2012) - Durrbach, Antoine; Jacquet, Antoine; Francois, Helene; Charpentier, Bernard
Allogenic organ transplantations are limited by drug-associated toxicity and the occurrence of antibody-mediated rejection or chronic rejection. The development of immunosuppressants that have minimal adverse and nephrotoxic effects is important to improve outcomes after organ transplantation. Several promising new compounds, based on our improved understanding of the molecular mechanisms of rejection, have been or are being developed to prevent acute and chronic transplant rejection. However, these new molecules need to be evaluated for their safety and to ensure they do not increase the risk of developing infections or tumors in transplant patients. Among them, belatacept (LEA29Y) is a new CD28 pathway-blocking reagent that has been developed as an alternative to calcineurin inhibitors. Belatacept is a recombinant and modified molecule (CTLA4–Ig) that interferes with the second activation signal of T lymphocytes, thereby causing a CD28–CD80/86 blockade. In this paper, we review the recently published results on belatacept-based regimens in renal transplant recipients.